White Matter Integrity in Tanzanian Children With Sickle Cell Anemia: A Diffusion Tensor Imaging Study. Issue 4 (April 2020) - Jacob, Mboka; Stotesbury, Hanne; Kawadler, Jamie M.; Lapadaire, Winok; Saunders, Dawn E.; Sangeda, Raphael Z.; Chamba, Clara; Kazema, Ramadhan; Makani, Julie; Kirkham, Fenella J.; Clark, Chris A.
Abstract : Background and Purpose—: Widespread reductions in white matter integrity are associated with cognitive dysfunction in sickle cell anemia. Silent cerebral infarction (SCI), vasculopathy (VSC), and low hemoglobin concentration (Hb) are implicated; we aimed to determine independent contributions to microstructural white matter injury and whether white matter integrity differs across arterial territories. Methods—: Sixty two children with sickle cell anemia aged 6 to 19 years were prospectively studied at Muhimbili National Hospital, Tanzania. SCI± and VSC± were identified on magnetic resonance imaging (MRI)/magnetic resonance angiography (MRA) scans by 2 neuroradiologists. Tract-based spatial statistics tested for voxel-wise differences in diffusion tensor imaging metrics (ie, fractional anisotropy, mean diffusivity, radial diffusivity, and axial diffusivity) between SCI± and VSC± groups, with correlations between diffusion tensor imaging metrics and Hb. In tract-based spatial statistics analyses, potentially mediating factors (ie, age, sex, as well as Hb, SCI, and/or vasculopathy) were covariates. Differences in mean diffusion tensor imaging metrics across regions of interest in arterial territories were explored. Results—: Compared with SCI− patients (n=45), SCI+ patients (n=17) exhibited increased radial diffusivity in multiple regions; negative relationships were observed between mean diffusivity, axial diffusivity, and Hb ( P <0.005). Compared with VSC− patients (n=49), mild (n=6) or moderate (n=7) VSC+ patients exhibited reduced fractional anisotropy in widespread regions ( P <0.05) including the anterior longitudinal fasciculi, corpus callosum, internal capsule, corona radiata, and corticospinal tracts. Overall, the posterior cerebral arterial territory had higher mean mean diffusivity and mean radial diffusivity than the anterior and middle cerebral arterial territories, although no patient had vasculopathy in this area. There was an interaction between territory and vasculopathy. Conclusions—: SCI, vasculopathy, and Hb are independent risk factors, and thus treatment targets, for diffuse white matter injury in patients with sickle cell anemia. Exacerbation of hemodynamic stress may play a role.